An Evaluation on Dental Students’ Performance during the First Year of Covid-19 Pandemic - Hazira M Yusof; Nusima Mohamed; Wan Nor Syariza Wan Ali (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 01-2021) [April 2021]